China's Maritime Silk Road and Small States: Lessons from the Case of Djibouti. Issue 122 (3rd March 2020) - Styan, David
ABSTRACT: This article sheds light on the factors shaping China's Maritime Silk Road Initiative (MSRI) in small states through a study of Djibouti and the MSRI. It also analyses the establishment of China's first overseas military base and thus evaluates the military-security implications of Chinese MSRI ports. Among other things, it shows that we need to conceive the locational value of MSRI participants more richly, that the existence of an authoritarian partner has advantages for China, but does not necessarily drive MSRI activities, and that small MSRI states have agency vis-à-vis China. It suggests, too, there is a template of Chinese port development and that it should not be assumed that China is intentionally wielding the 'debt trap' to gain equity.